Interview with Peter Schweitzer: “If You No Longer Allow for the Possibility of Alterity, You are Limiting Your Options of Analyzing the World(s)” (interviewed by Elena Gudova) - Gudova, Elena; Schweizer, Peter (Экономическая социология, 2017)
In this interview, Peter Schweitzer discusses his interest in Siberian studies and Arctic research and addresses the so-called “ontological turn” within recent anthropological debates. His earlier academic interests in the hunting and gathering societies of Chukotka and northeastern Siberia took him to the University of Alaska Fairbanks and led to his eventual cooperation with natural science scholars examining climate change in the Arctic region especially in Alaska. Schweitzer’s current research project, “Configurations of Remoteness,” analyzes the construction of the Baykal-Amur Mainline [BAM] as an example of the influence of (transportation) infrastructure on the ecological and social conditions of a region. The research focuses on the mobility and sociality of people living in areas affected by the BAM and questions the construction of remoteness by observing shifts in that mobility and sociality among builders of the BAM. Schweitzer also discusses the current anthropological interest in ontology and suggests that, along with the more-than-human perspective in some of the social sciences, this enables scholars to go beyond the deconstruction of the “other” to allow for “alterity” as a tool in analyzing the world or worlds. The notion of different worlds (and one culture) is more radical than conceiving of one world from different cultural perspectives. A broader approach to human-environment relations that incorporates alterity offers more fruitful tools for researchers, expanding their analytical possibilities.